Repair of claimed non-understanding of word meaning in online discussion forum interaction - Myrendal, Jenny (Dialogue and discourse, 2025)
This article describes how participants in online discussion forums manage claimed non-understanding of word meaning, specifically when one participant displays insufficient understanding by requesting meta-linguistic clarification. Claimed non-understanding refers to cases where a participant signals a lack of understanding in a way that invites repair. By engaging in a short word meaning negotiation sequence, the participants collaboratively repair the issue of claimed non-understanding and can move on with the discussion on topic. In some cases, however, participants behave in ways that break the normative pattern of interaction and do not enter into the anticipated sequence of repair dealing with the lack of understanding. The analysis of these deviant cases reveals the participants’ own normative orientations in repair of claimed non-understanding of word meaning, and thus provide evidence that there is an underlying organization of repair dealing with such issues in online discussion forum interaction.